Synthesis of Compounds Acetyl Vanilat as Analgesic Compound Components - Iskandar, Damayanti; Prabawati, Susy Yunita (Jurnal ILMU DASAR, 2016)
Acetyl vanillate was synthesized to become an analgesic compound was conducted in two stages.The first stage is oxidation vanillin using Tollens reagent. The result of the oxidation wascharacterized by melting point and FTIR. The second stage, vanillic acid was acetylated usingacetic acid anhydrous under two conditions, that are acid and base using H2SO4 and NaOH 10%,respectively. Two difference products from those processes were characterized using FTIR and1H-NMR. The result of the melting point vanillic acid test showed 204°C and the standard is210°C. Vanilline was successfully oxidized, based on comparison FTIR spectra between vanillineand its precursor that showed no functional group of C-H aldehyde at 2,700-2,800 cm-1. Thecharacteristics FTIR spectra under base conditions showed no absorption of functional group ‒OHthat substituted by an acetyl group. So that, the base catalyst indicated no product of the expectedcompound. The product under acidic compounds have the characteristic yellow crystals with amelting point of 130°C. Characteristics of FTIR showed no width absorption at wave number 3400cm-1 and evidenced by 1H-NMR spectra. Shift peak at 2.342 ppm was an absorption acetylcompounds. It was concluded that acetylation of acetyl vanillate compounds under acidicconditions to produce the expected product.Keywords: vanilin, vanilic acid, acetylation